Educating the Business Graduate of the 21st Century: Communication for a Globalized World - Briguglio, Carmela (International Society for Exploring Teaching and Learning, 2007)
This article examines current business communication education in higher education, particularly in regard to English as a global language. The discussion is situated at the intersection of business communication, intercultural communication, and internationalization of higher education, and the article draws on research from all three fields. The article questions why not enough use is being made of existing cultural diversity in university classrooms, and it suggests a variety of pedagogical strategies which will enable teachers to build on the cultural and linguistic strengths of their students to develop intercultural communication competence. These new directions for intercultural business communication will equip business graduates to operate successfully in a globalized world.